An intersectional analysis of the systemic discrimination confronting LGBTQ+ individuals in the Middle East: the cases of Iran, Turkey, and Egypt - Bekker, Simone (University of the Free State, 2023)
𝑬𝒏𝒈𝒍𝒊𝒔𝒉 The road to equality is not straight, and for LGBTQ+ individuals the road holds various intersections of discrimination. Aspects such as identity and gender have directly impacted the level to which individuals are shunned by their families, communities, and social nexus. Although discrimination against LGBTI people undermines the human rights principles outlined in the Universal Declaration of Human Rights, discrimination and violence against people in the LGBTI community are all too common. Homophobic, biphobic, and transphobic attitudes remain deeply embedded in many cultures around the world. A significant amount of research on intersectionality concentrates primarily on African American women and other women of colour, and it seems that the research on intersectionality has not sufficiently addressed the lives of Middle Eastern LGBTQ+ individuals. Often, LGBTQ+ individuals are misrepresented by selected states from the region at international forums such as the United Nations General Assembly and Human Right Council. Using claims based on religious and cultural values, selected states undermine the rights of LGBTQ+ individuals, and Arab-speaking and Muslim majority states seem to form a homogenous entity with a uniform view on LGBTQ people. All LGBTQ+ members are assumed to be faced with the same systemic discrimination and to have the same human rights needs and experiences. For this reason, intersections of multiple systems of oppression are not recognised and the interests of some are privileged while the experiences of others are marginalised. To address this gap, this study uses an intersectional framework which notes that the LGBTQ+ community in the Middle East is not a singular entity, and even though conditions differ based on country, gender, and from individual to individual, as a whole, the LGBTQ community in the region has not been granted the “freedoms” linked to Western ideals of homosexual progress, such as open displays of romantic affection, gay marriage, and other superficial indications of acceptance in society. This study analyses differences of experiences of LGBTQ+ individuals within three separate case studies, namely Iran, Turkey, and Egypt. It does so by applying an intersectional lens to recognise the ways in which different social identities produce intersecting systems of privilege or oppression, and how these systems create different lived experiences, and/or common experiences within a social context. This dissertation is a qualitative study which utilises case study methodology to analyse the existing literature related to the topics. Discrimination and violence against LGBTQ+ individuals directly undermine the human rights principles outlined in the Universal Declaration of Human Rights. The fact that so many instances of such violation continue to go unchallenged is testimony to the deep cultural roots of homophobia, biphobia, and transphobia. ___________________________________________________________________

𝑨𝒇𝒓𝒊𝒌𝒂𝒂𝒏𝒔 Die pad na gelykheid is nie reguit nie, en vir LGBTQ+ lede hou die lewe verskillende kruisings van diskriminasie in. Aspekte soos identiteit en geslag beïnvloed die mate waartoe individue verwerp word deur hul gesinne, gemeenskappe, en sosiale nexus direk. Diskriminasie teen LGBTI+ lede ondermyn die menseregtebeginsels soos uiteengesit in die Universele Verklaring van Menseregte. Tog kom diskriminasie en geweld teen mense in die LGBTQ+ gemeenskap gereeld voor. Homofobiese, bifobiese en transfobiese houdings bly diep ingebed in baie kulture regoor die wêreld. 'n Beduidende hoeveelheid navorsing oor interseksionele of kruispuntbesonderhede konsentreer hoofsaaklik op Afro-Amerikaanse vroue en ander vroue van kleur, en dit wil voorkom asof die navorsing oor interseksionaliteit nog nie die lewens van Midde-Oosterse LGBTQ+ individue voldoende aangespreek het nie. Dikwels word LGBTQ + individue deur geselekteerde state uit die streek verkeerd voorgestel op internasionale forums soos die Verenigde Nasies se Algemene Vergadering en die Raad vir Menseregte. Deur gebruik te maak van eise gebaseer op godsdienstige en kulturele waardes, ondermyn geselekteerde state die regte van LGBTQ + individue, en Arabiessprekende en Moslem-meerderheid vorm skynbaar 'n homogene entiteit met 'n eenvormige siening oor LGBTQ-mense. Daar word aanvaar dat alle LGBTQ+ lede dieselfde sistemiese diskriminasie ondervind en dieselfde menseregte behoeftes en ervarings het. Om hierdie rede word kruisings van veelvuldige stelsels van onderdrukking nie erken nie en word die belange van sommige bevoorreg terwyl die ervarings van ander gemarginaliseer word. Om hierdie leemte aan te spreek, gebruik hierdie studie 'n kruisingsraamwerk wat daarop dui dat die LGBTQ + -gemeenskap in die Midde-Ooste nie 'n enkelvoudige entiteit is nie, en selfs al verskil toestande op grond van land, geslag, en van individu tot individu, word daar aan die LGBTQ-gemeenskap as geheel in die streek nie die “ vryhede ” toegeken wat aan Westerse ideale van homoseksuele vooruitgang gekoppel word nie, soos openlike betoning van romantiese toegeneentheid, gay huwelike en ander oppervlakkige aanduidings van aanvaarding in die samelewing. Hierdie studie ontleed verskille in ervarings van LGBTQ + individue in drie afsonderlike gevallestudies, naamlik Iran, Turkye en Egipte. 'n Interseksionele lens word toegepas om to recognise the ways in which different social identities produce intersecting systems of privilege or oppression die maniere waarop verskillende sosiale identiteite kruispunt-stelsels van voorreg of onderdrukking produseer, raak te sien, asook hoe hierdie stelsels verskillende ervarings skep en/of lei tot algemene ervarings binne 'n sosiale konteks. Hierdie proefskrif is 'n kwalitatiewe studie wat gebruik maak van gevallestudiemetodologie om die bestaande literatuur wat met die onderwerpe verband hou, te ontleed. Diskriminasie en geweld teen LGBTQ + individue ondermyn direk die menseregte-beginsels soos uiteengesit in die Universele Verklaring van Menseregte. Die feit dat soveel voorvalle van geweld steeds onverhindered voorkom, bevestig dat homofobie, bifobie, en transfobie diep in die kultuur gewortel is. ___________________________________________________________________
Dissertation(M.A.(Political Studies and Governance))--University of the Free State, 2023
Keywords: LGBTQ+; Intersectionality; Discrimination; Human rights; Iran; Turkey; Egypt; Lesbian; Gay; Homophobia; Violence; Sexual orientation; Gender identity